Development of a Bayesian Network for the Prognosis of Head Injuries using Graphical Model Selection Techniques - Sakellaropoulos, G. C.; Nikiforidis, G. C. (Methods of Information in Medicine, 1999)
The assessment of a head-injured patient’s prognosis is a task that involves the evaluation of diverse sources of information. In this study we propose an analytical approach, using a Bayesian Network (BN), of combining the available evidence. The BN’s structure and parameters are derived by learning techniques applied to a database (600 records) of seven clinical and laboratory findings. The BN produces quantitative estimations of the prognosis after 24 hours for head-injured patients in the outpatients department. Alternative models are compared and their performance is tested against the success rate of an expert neurosurgeon.
Keywords: Bayesian Networks; Head Injuries; Prognosis; Learning Models